A CMOS image sensor with dark-current cancellation and dynamic sensitivity operations. - Hsiu-Yu Cheng
An ultralow dark-signal and high-sensitivity pixel has been developed for an embedded active-pixel CMOS image sensor by using a standard 0.35-μm CMOS logic process. To achieve in-pixel dark-current cancellation, we developed a combined photogate/photodiode photon-sensing device with a novel operation scheme. The experimental results demonstrate that the severe dark signal degradation of a CMOS active pixel sensor is reduced more than an order of magnitude. Through varying the bias conditions on the photogate, dynamic sensitivity can be obtained to increase maximum allowable illumination level. Combining the above two operation schemes, the dynamic range of this new cell can be extended by more than 20×.
Keywords: 0.35 micron; CMOS APS; Bias conditions variation; Combined photogate/photodiode photon-sensing device; Dark signal degradation; Dark-current cancellation; Dynamic sensitivity; Dynamic sensitivity operations; Embedded active-pixel CMOS image sensor; High-sensitivity pixel; Standard CMOS logic process; Ultralow dark-signal pixel